Analisis Manajemen Kinerja Badan Penanggulangan Bencana Daerah Kabupaten Musi Rawas Utara dalam Mitigasi Bencana Banjir - Idanja, Ragil; Fitri Helmi, Rahmadhona (PUBLICNESS: Journal of Public Administration Studies, 2023)
Geographical conditions of the lowlands, resulting in North Musi Rawas Regency (Muratara) as an area prone to flooding. Handling this, the Regional Disaster Management Agency (BPBD) of Muratara Regency is authorized to carry out disaster management tasks, including flood disaster mitigation as a prevention effort to reduce potential losses due to future disasters. This study aims to analyze the implementation and constraints of the performance management of BPBD Muratara Regency in flood disaster mitigation in Muratara Regency. The results showed that the performance management of BPBD Muratara in flood disaster mitigation with four stages, namely determining approaches, policies, strategies and flood disaster mitigation activities, has not been well implemented. This can be seen by the fact that there are no programs and activities focused on reducing disaster risk, lack of facilities and infrastructure, not maximizing human resource training activities, lack of expert / civil servants, unavailability of Early Warning System (EWS) and not maximizing coordination and collaboration between stakeholders. In addition, there are also obstacles encountered such as the absence of a Disaster Management Plan (RPB).  RPB is very much needed in flood disaster mitigation. Because it contains disaster risk assessments, contingency plans, budgets, programs/activities, coordination and collaboration between stakeholders involved.